2002
DOI: 10.1021/bi011361+
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Guanosine Triphosphate/Diphosphate Requirements for Transit Peptide Recognition by the Cytosolic Domain of the Chloroplast Outer Envelope Receptor, Toc34

Abstract: Toc34 is a transmembrane protein located in the outer envelope membrane of chloroplasts and involved in transit peptide recognition. The cytosolic region of Toc34 reveals 34% alpha-helical and 26% beta-strand structure and is stabilized by intramolecular electrostatic interaction. Toc34 binds both chloroplast preproteins and isolated transit peptides in a guanosine triphosphate- (GTP-) dependent mechanism. In this study we demonstrate that the soluble, cytosolic domain of Toc34 (Toc34deltaTM) functions as rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…In the first model, Toc34 and Toc159 remain stably associated with the outer envelope membrane and interact with incident preproteins directly, much like the mitochondrial protein import receptors Tom20 and Tom22 (Pfanner and Geissler, 2001). In support of this model, preproteins can be cross-linked to pea Toc34 (psToc34) and/or psToc159 very early during import into pea chloroplasts (Perry and Keegstra, 1994;Ma et al, 1996;Kouranov and Schnell, 1997), and a direct and specific interaction between preproteins and psToc34 has been observed in vitro (Sveshnikova et al, 2000;Schleiff et al, 2002). However, not all cross-linking studies resulted in the identification of psToc34 (Perry and Keegstra, 1994;Ma et al, 1996), and in those that did, psToc34 appeared to interact with the mature region of the preprotein rather than with the transit peptide, as would be expected of a receptor (Kouranov and Schnell, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…In the first model, Toc34 and Toc159 remain stably associated with the outer envelope membrane and interact with incident preproteins directly, much like the mitochondrial protein import receptors Tom20 and Tom22 (Pfanner and Geissler, 2001). In support of this model, preproteins can be cross-linked to pea Toc34 (psToc34) and/or psToc159 very early during import into pea chloroplasts (Perry and Keegstra, 1994;Ma et al, 1996;Kouranov and Schnell, 1997), and a direct and specific interaction between preproteins and psToc34 has been observed in vitro (Sveshnikova et al, 2000;Schleiff et al, 2002). However, not all cross-linking studies resulted in the identification of psToc34 (Perry and Keegstra, 1994;Ma et al, 1996), and in those that did, psToc34 appeared to interact with the mature region of the preprotein rather than with the transit peptide, as would be expected of a receptor (Kouranov and Schnell, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…This could provide a part of the molecular switch that triggers the insertion of Toc159 and the initiation of preprotein translocation. Others have proposed that Toc33/34 acts as the primary transit peptide receptor and that Toc159 functions only as a component of the translocation motor (7,12,25). However, all current data can be reconciled by the model in which the two Toc GTPases act coordinately to regulate transit peptide recognition and initiate membrane translocation by interacting directly with each other in a manner regulated by their intrinsic GTPase activities.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Initial studies demonstrated that Toc34 binds to a variety of chloroplast preproteins, suggesting that it functions as a receptor for protein import [9]. Phosphorylation of the transit peptide, although not essential for preprotein recognition by Toc34, promotes high-affinity binding to Toc34 [10].…”
Section: The Targeting and Motor Hypothesesmentioning
confidence: 99%